Relationship of Atrial Fibrillation to Outcomes in Patients Hospitalized for Chronic Obstructive Pulmonary Disease Exacerbation - Abdullah, Abdullah Sayied (J Atr Fibrillation, 2019)
INTRODUCTION: Chronic Obstructive Pulmonary Disease (COPD) is a major cause of hospitalization and is associated with an increased incidence of atrial fibrillation (AF). The impact of AF on in-hospital outcomes, including mortality, in patients hospitalized for COPD exacerbation is not well elucidated. METHODS: We used the National Inpatient Sample database to examine discharges with the primary diagnosis of COPD exacerbation and compared mortality, length of stay and costs in patients with AF compared to those without AF. The study adjusted the outcomes for known cardiovascular risk factors and confounders using logistic regression and propensity score matching analysis. RESULTS: Among 1,377,795 discharges with COPD exacerbation, 16.6% had AF. Patients with AF were older and had more comorbidities. Mortality was higher (2.4%) in the AF group than in the no AF group (1%), p <0.001. After adjustment to age, sex and confounders, AF remained an independent predictor for mortality, OR:1.44 (95% CI 133 – 1.56, p <0.001), prolonged length of stay, OR:1.63 (95% CI 1.57 – 1.69, p <0.001) and increased cost, OR: 1.45 (95% CI: 1.40 – 1.49, p <0.001). CONCLUSIONS: among patients with COPD exacerbation, AF was associated with increased mortality and higher resource utilization.